2021
DOI: 10.1161/jaha.121.021170
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Cause of Death Via Comprehensive Autopsy and Whole Exome Molecular Sequencing in People With Epilepsy and Sudden Unexpected Death

Abstract: Background Sudden cardiac arrest is the leading mode of death in the United States. Epilepsy affects 1% of Americans; yet epidemiological data show a prevalence of 4% in cases of sudden cardiac arrest. Sudden unexpected death in epilepsy (SUDEP) may share features with sudden cardiac arrest. The objective of this study was to report autopsy and genomic findings in a large cohort of SUDEP cases. Methods and Results Mayo Clinic Sudden Death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
0
14
0
2
Order By: Relevance
“…Whole‐exome sequencing (WES) and bioinformatics analyses in 3 affected family members (II‐5, III‐11, and III‐16) and 2 unaffected family members (II‐6 and III‐14) from Family 1 were completed as described elsewhere. 59 , 60 , 61 , 62 Briefly, for each family member selected to undergo WES, 3 μg of genomic DNA were used for construction of a whole exome library, which was captured with the SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA) following the manufacturer's manual. The captured exome libraries were sequenced on the Illumina HiSeq 2000 Genome Analyzer (Illumina, San Diego, CA), with the HiSeq Sequencing Kit (Illumina) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Whole‐exome sequencing (WES) and bioinformatics analyses in 3 affected family members (II‐5, III‐11, and III‐16) and 2 unaffected family members (II‐6 and III‐14) from Family 1 were completed as described elsewhere. 59 , 60 , 61 , 62 Briefly, for each family member selected to undergo WES, 3 μg of genomic DNA were used for construction of a whole exome library, which was captured with the SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA) following the manufacturer's manual. The captured exome libraries were sequenced on the Illumina HiSeq 2000 Genome Analyzer (Illumina, San Diego, CA), with the HiSeq Sequencing Kit (Illumina) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…DNA sequencing is another potential strategy to identify a child that is at risk to succumb to SUID. DNA sequencing has already identified genes related to cardiac, neurologic, and metabolic disorders that could be linked to SUID (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The early identification of high-risk genes could potentially also be important for preventing mortality and morbidity for children that survive beyond the one-year window for SUID.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using genetic testing have revealed a significant portion (∼12-30%) of children/young adults with sudden cardiac death (SCD) that have pathogenic rare variants in genes associated with arrhythmic syndromes and cardiomyopathy 6, 8 . In addition, rare variants in genes associated with epilepsy have also been associated with SCA in the young 9 .…”
Section: Introductionmentioning
confidence: 99%